2016
DOI: 10.5152/iao.2016.1732
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme (ACE) I/D and Alpha-Adducin (ADD1) G460W Gene Polymorphisms in Turkish Patients with Severe Chronic Tinnitus

Abstract: OBJECTIVE:Tinnitus is described as a disturbing sound sensation in the absence of external stimulation. We aimed to investigate whether there is any relationship between severe chronic tinnitus and angiotensin-converting enzyme (ACE) I/D and α-adducin (ADD1) G460W gene polymorphisms. MATERIALS and METHODS:The patient group and control group consisted of 89 and 104 individuals, respectively. The evaluation of tinnitus was performed using the Strukturiertes Tinnitus-Interview (STI). The Tinnitus Handicap Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(38 reference statements)
0
9
0
1
Order By: Relevance
“…Tinnitus candidate gene selection has included genes enriched in cardiovascular function ( ACE, ADD1 ), neurotrophic factors ( BDNF, GDNF ), ion recycling pathways ( KCNE1, KCNE3, SLC12A2 ), GABA B receptor subunit ( KCTD12 ), and serotonin receptor/transporter ( HTR1A, SLC6A4 ) function. Presently, nine case-control studies have examined a combined total of 18 genes that are summarized in Table 2 (Kleinjung et al, 2006; Deniz et al, 2010; Sand et al, 2010, 2011, 2012a,b; Pawełczyk et al, 2012; Orenay-Boyacioglu et al, 2016; Yüce et al, 2016). For brevity, we describe selected case-control association studies with potentially significant results.…”
Section: Complex Genetics Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tinnitus candidate gene selection has included genes enriched in cardiovascular function ( ACE, ADD1 ), neurotrophic factors ( BDNF, GDNF ), ion recycling pathways ( KCNE1, KCNE3, SLC12A2 ), GABA B receptor subunit ( KCTD12 ), and serotonin receptor/transporter ( HTR1A, SLC6A4 ) function. Presently, nine case-control studies have examined a combined total of 18 genes that are summarized in Table 2 (Kleinjung et al, 2006; Deniz et al, 2010; Sand et al, 2010, 2011, 2012a,b; Pawełczyk et al, 2012; Orenay-Boyacioglu et al, 2016; Yüce et al, 2016). For brevity, we describe selected case-control association studies with potentially significant results.…”
Section: Complex Genetics Approachesmentioning
confidence: 99%
“…Hypertension-associated auditory primary lesion sites are the organ of Corti and stria vascularis (Gates et al, 1993). An association study investigated the relationship between severe chronic tinnitus and the p.G460W polymorphism in 89 patients with severe chronic tinnitus and 104 age-matched Turkish-Caucasian controls (Yüce et al, 2016). Clinical tinnitus evaluation and severity assessment were performed by the Structured Tinnitus Interview and the Tinnitus Handicap Inventory, respectively.…”
Section: Complex Genetics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Este tipo de estudio sólo permite identificar variantes ligadas a un gen concreto y requieren estudios a escala genómica previa para proponer genes candidatos. Por otra parte, la selección de variantes puede presentar un sesgo de selección, por la asociación entre el marcador genético en estudio y la variante genética de riesgo verdadera (desequilibrio de ligamiento), resultando difícil determinar cuál es la variante que confiere el riesgo para la fenotipo (21) Hasta ahora se han realizado 9 estudios de casos-control con 18 genes candidatos (10)(11)(12)(13)(22)(23)(24)(25)(26). (Tabla 1).…”
Section: Genética De Los Acúfenosunclassified
“…Identification of the genetic variants involved in tinnitus would help reveal the nature of the mechanisms involved in generating tinnitus after hearing loss, a pre-requisite for development of treatments. Previous pilot genome-wide association studies and candidate gene studies for tinnitus 10; 13-18 have lacked sufficient power to establish specific genetic risk factors but the relatively high heritability demonstrates there is potential to use such approaches to reveal the underlying mechanisms 9; 10 . On this basis we performed a genome-wide association study using self-reported tinnitus available from 172,608 UK Biobank (UKBB) 19 volunteers.…”
Section: Introductionmentioning
confidence: 99%